A Qualitative Examination of Barriers and Facilitators to Providing Pedagogical Training for Doctoral Students in Behavioral and Social Sciences Programs at US Schools of Public Health. (December 2022) - Walker, Elizabeth Reisinger; Lederer, Alyssa M.; Stolow, Jeni A.
There is increasing attention regarding the preparation of doctoral students in schools of public health (SPH) to teach; however, few studies have examined pedagogical preparation for doctoral students in public health-related disciplines. This study aimed to describe the pedagogical training and experiences available for doctoral students in behavioral and social sciences (BSS) programs in SPH and examine the facilitators and barriers to offering pedagogical training and experiences. Qualitative semi-structured interviews were completed with 13 pedagogy instructors, program directors, or administrators in SPH with BSS doctoral programs. Data were analyzed using thematic analysis. Just over half (54%) of the doctoral programs offered or planned to offer a pedagogy course in their curricula. Doctoral students in most programs had access to other teaching training opportunities, most commonly through university centers for teaching and learning. All doctoral programs required or provided students with the option to serve as a teaching assistant and, in some cases, instructor. Key factors contributing to if pedagogical training and experiences were available in the doctoral programs were the degree of priority placed on teaching preparation for doctoral students; logistic challenges, such as time and funding constraints; the level of need to fill teaching assistant and instructor positions; and competencies requiring teaching training for Doctor of Public Health students. Doctoral programs considering changes or expansion of pedagogical training and experiences should consider how to overcome common barriers and leverage facilitators in order to provide students with the best possible pedagogical preparation for both academic and non-academic careers.